Neuroanatomy and transgenic technologies - Laurent Gautron (Frontiers Research Topics, 2015)
Neuroanatomists increasingly rely on techniques enabling them to manipulate genes in defined brain cell populations. In particular, engineered transgenes, which encode a variety of fluorescent reporter proteins can be inserted into the genome or delivered into desired brain regions using viral vectors, thereby allowing the labeling of molecularly-defined populations of neurons and/or glial cells. Transgenic technology can also be used to selectively delete genes in targeted neuronal populations or bi-directionally modulate their electrical excitability using optogenetic or chemogenetic techniques. One of the primary advantages of using transgenic reagents is to simplify the identification and tracing of targeted population of brain cells, which can be laborious using traditional techniques in neuroanatomy. In this research topic, we assembled up-to-date reviews and original articles that demonstrate the versatility and power of transgenic tools in advancing our knowledge of the nervous system, with a special emphasis on the application of transgenic technology to neuroanatomical questions.